Understanding the emergence of STI policies in the EU: The genesis of EU security research and the role of the EU commission as policy entrepreneur - Jakob Edler; Andrew D. James (The University of Manchester, Manchester Business School, 2012)
This paper contributes to our understanding of agenda shaping and decision making in science, technology and innovation policy and the role of political entrepreneurship in this process. It does so by looking at the emergence of a particular new STI policy area, security research, in the specific political setting of the European Union. This emergence was in many ways a remarkable new development in EU STI policy and is a puzzle that has yet to be analysed. This paper asks why, how, by whom and in what form security research was put on to the policy agenda and then finally included in the Framework Programme at this specific point in time. The paper emphasises the interplay between discursive mechanisms and power and interest based negotiations. The analysis focuses on the role of the European Commission as policy entrepreneur in pushing the topic onto the agenda and through the decision making process. The main argument is that the Commission was the originator of the Security theme and that the institutional role, entrepreneurial competencies and discursive skills of the Commission helped to capture and utilise a window of opportunity and orchestrate change. However, diverse interests in Member States and in the EU Parliament as well as the lack of a broader normative consensus severely limited the scope of the Security theme. The Commission was thus a constrained entrepreneur, successful in pushing a new area - security research - onto the agenda, but falling short of altering the landscape of defence research in Europe. To explain this complex story of policy change in STI policy and to understand the role and limitations of the European Commission as policy entrepreneur, the paper builds on neo-institutional and European integration theories. This paper makes four contributions: First, it delivers a more complete picture of the current landscape of European research policy, as the Security theme under the seventh Framework Programme has not been discussed in any great detail so far. This serves, second, to illustrate and further develop our understanding of the levers and limitations of policy entrepreneurs in STI policy making. Thirdly, the paper highlights the meaning of ambiguity in discursive development of policy and, finally and most generally, demonstrates how important it is to understand the interplay of ideas and interests in STI policy and the meaning of policy origins.
Keywords: 330; EU-Forschungspolitik; Nationale Sicherheit; Wissenschaftsforschung; Policy-Ansatz; EU-Staaten